Sodium-supplementing additive, preparation method thereof and application of sodium-supplementing additive in sodium-ion battery
By using a core-shell structured sodium-replenishing additive coated with sodium citrate and dihydrogen phosphate in the cathode material of sodium-ion batteries, the performance degradation problem caused by the increase of residual alkali value in sodium-ion batteries has been solved, and the stability and performance of the batteries have been improved.
Patent Information
- Application Number
- CN202510974246.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-10-24
AI Technical Summary
Adding sodium-supplementing additives to existing sodium-ion battery cathode materials can lead to an increase in residual alkali value, affecting the insertion and extraction of sodium ions, resulting in problems such as poor rate performance, reduced cycle life, and increased internal resistance.
Sodium citrate is used as a sodium supplement additive, and dihydrogen phosphate is coated on its surface to form a core-shell structure. The alkalinity of sodium citrate and the acidity of dihydrogen phosphate are used to neutralize the sodium citrate, thereby preventing the residual alkali value from increasing and improving the stability and performance of the battery.
By designing a core-shell structure, side reactions are suppressed, battery stability and performance are improved, battery internal resistance is reduced, sodium ion insertion and extraction processes are improved, and battery cycle life and rate performance are enhanced.
Smart Images

Figure CN120834209A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of sodium ion batteries, and particularly relates to a sodium supplementing additive, a preparation method thereof and application of the sodium supplementing additive in a sodium ion battery. BACKGROUND
[0002] With the increasing demand for clean energy worldwide, efficient energy storage technologies for clean energy such as solar and wind energy have become crucial. Although lithium ion batteries have been successful, the limited and uneven distribution of lithium resources have limited their large-scale application, so alternative energy storage technologies need to be found. Sodium ion batteries have become a potential sustainable energy storage solution because sodium has similar chemical properties to lithium, is abundant and widely distributed.
[0003] Sodium ion batteries operate on a similar principle to lithium ion batteries. At the present stage, hard carbon has become an excellent negative electrode material in sodium ion batteries due to its stable structure, excellent electrical conductivity and high sodium storage capacity, and has great potential for industrial application. However, hard carbon has many defects and a large specific surface area, which leads to more significant sodium ion irreversible loss caused by SEI formation and interface side reactions, affecting the energy density and cycle life of sodium ion batteries, and is particularly serious for sodium ion full batteries.
[0004] To solve the problem of sodium ion loss, researchers have adopted techniques such as positive electrode sodium supplementing and negative electrode sodium supplementing. In positive electrode sodium supplementing, the method of using a sodium-rich positive electrode is not conducive to industrial production because it is complicated to operate and involves the synthesis of new materials and is difficult. The method of adding a sodium supplementing additive has a wider application range and is easier to operate, and has more prospects for large-scale application. The sodium supplementing additives for positive electrode materials on the market are mostly inorganic salts such as NaN3, Na3PO4 and Na3P. However, these additives have some defects such as toxicity and poor thermal stability, and are easily decomposed at high temperatures, affecting the performance and safety of the battery. In addition, existing sodium supplementing additives can also cause the residual alkali value of the positive electrode material to be too high, which in turn causes many problems, such as increasing the chemical reaction activity inside the battery, bringing about thermal runaway and other safety risks; aggravating battery polarization, increasing internal resistance and reducing charge and discharge efficiency; making the positive electrode material prone to moisture absorption, caking or chemical changes during storage, affecting its stability and long-term performance; and adversely affecting homogenate stability, leading to particle precipitation, delamination and the like.
[0005] In view of the above, it is necessary to provide a new sodium supplementing additive and a preparation method thereof, which can keep the residual alkali value of the positive electrode material stable without affecting the electrical performance. SUMMARY
[0006] To this end, the technical problem to be solved by the present application is to overcome the problem that adding a sodium supplement additive in a sodium ion battery positive electrode material will increase the residual alkali value of the sodium ion battery positive electrode material, and the high residual alkali value will affect the embedding and de-embedding process of sodium ions, resulting in poor rate performance, reduced cycle, increased internal resistance and other problems.
[0007] To solve the above technical problems, the present application provides a sodium supplement additive, a preparation method thereof and an application thereof in a sodium ion battery. The sodium supplement additive is prepared from sodium citrate. Since sodium citrate is weakly alkaline, coating a weakly acidic dihydrogen phosphate salt on the outer layer can neutralize the alkalinity of sodium citrate to a certain extent, so that when sodium citrate is added as a sodium supplement additive to a sodium ion battery positive electrode material, the residual alkali value will not increase, thereby avoiding the reduction of battery capacity.
[0008] The first object of the present application is to provide a sodium supplement additive, which comprises a substrate and a coating layer coated on the surface of the substrate; the substrate comprises carbon nanotubes and sodium citrate loaded on the carbon nanotubes; and the coating layer is dihydrogen phosphate salt.
[0009] The mass ratio of the substrate to the coating layer is (90-99):(10-1);
[0010] The mass ratio of the carbon nanotubes to sodium citrate is (0.01-0.05):1.
[0011] In an embodiment of the present application, the dihydrogen phosphate salt is selected from one or more of sodium dihydrogen phosphate, potassium dihydrogen phosphate and calcium dihydrogen phosphate.
[0012] The second object of the present application is to provide a preparation method of the sodium supplement additive, which comprises the following steps:
[0013] S1, ball milling carbon nanotubes and sodium citrate in ethanol to obtain sodium citrate-loaded carbon nanotubes by heat treatment;
[0014] S2, dissolving the sodium citrate-loaded carbon nanotubes in ethanol, adding dihydrogen phosphate salt under a protective atmosphere to react, and drying to obtain the sodium supplement additive.
[0015] In an embodiment of the present application, in S1, the rotation speed of the ball milling is 200 r / min-400 r / min, and the time is 2 h-4 h.
[0016] In an embodiment of the present application, in S1, the heat treatment is first heated to 30-40℃ at a rate of 1℃ / min-2℃ / min and kept for 55 min-65 min under a protective atmosphere, and then heated to 155℃-165℃ at a rate of 1℃ / min-2℃ / min and kept for 3 h-6 h.
[0017] In one embodiment of the present application, in S2, the reaction time is 1h-4h.
[0018] In one embodiment of the present application, in S2, the drying temperature is 115℃-125℃, and the time is 4h-8h.
[0019] A third object of the present application is to provide a sodium-ion battery cathode, which comprises, in mass parts, 5-10 parts of the sodium supplementing additive, 70-85 parts of a sodium-ion battery cathode material, 1-10 parts of a conductive agent, and 1-10 parts of a binder.
[0020] In one embodiment of the present application, the sodium-ion battery cathode material is selected from one or more of sodium nickel manganese acid, sodium nickel iron manganese acid, iron sulfate, sodium vanadium phosphate, sodium copper iron manganese acid, and sodium iron pyrophosphate; the conductive agent is one or more of carbon nanotubes, acetylene black, conductive carbon black, conductive graphite, carbon fibers, and graphene; and the binder is one or more of polyolefin, fluorine-containing resin, polypropylene resin, and rubber.
[0021] A fourth object of the present application is to provide a sodium-ion battery comprising the sodium-ion battery cathode.
[0022] The technical solution of the present application has the following advantages compared with the prior art:
[0023] (1) The sodium supplementing additive has a core-shell structure, with carbon nanotubes loaded with sodium citrate as the core and dihydrogen phosphate as the shell. The carbon nanotubes as the carrier can enhance the overall conductivity of the material, improve the electronic conductivity, and reduce the internal resistance of the battery, thereby improving the rate and cycle performance of the battery. Sodium citrate is alkaline, and if directly added to the cathode material, it will cause an increase in residual alkali, which will in turn trigger some side reactions, affect the embedding and extraction process of sodium ions, and cause the battery capacity to decrease and the rate performance to deteriorate. In addition, residual alkali will also react with the electrolyte to produce undesirable by-products, affecting the stability and life of the electrolyte. By coating dihydrogen phosphate, these side reactions can be inhibited, thereby improving the stability and performance of the battery. For example, it can reduce the reaction of alkali with electrolyte, reduce the decomposition of electrolyte and the increase of battery internal resistance; it can also prevent sodium citrate from directly contacting other components, reducing the release of alkali; it can change the surface properties of sodium citrate, reducing its alkalinity; it can provide a certain barrier effect, reducing the reaction of alkali with the cathode material. Furthermore, sodium citrate and potassium dihydrogen phosphate will generate P / N / O co-doped carbon at high temperature, and the composite produced in cooperation with carbon nanotubes can improve the specific capacity and cycle stability.
[0024] (2) The preparation method is simple, the material price is relatively low, and it is convenient for subsequent production and scaling up. BRIEF DESCRIPTION OF DRAWINGS
[0025] For the purpose of making the content of the present application more easily understood, the present application will be further described in detail below according to the specific embodiments of the present application and in conjunction with the accompanying drawings, in which:
[0026] Figure 1 Charge-discharge curve of button cell prepared by the sodium supplement additive of Example 1 in Test Example 2 of the present application;
[0027] Figure 2 Charge-discharge curve of button cell prepared by the sodium supplement additive of Example 2 in Test Example 2 of the present application;
[0028] Figure 3 Charge-discharge curve of button cell prepared by the sodium supplement additive of Example 3 in Test Example 2 of the present application;
[0029] Figure 4 Charge-discharge curve of button cell prepared by the sodium supplement additive of Comparative Example 1 in Test Example 2 of the present application;
[0030] Figure 5 Charge-discharge curve of button cell prepared by the sodium supplement additive of Comparative Example 2 in Test Example 2 of the present application;
[0031] Figure 6 Charge-discharge curve of button cell prepared by the sodium supplement additive of Comparative Example 3 in Test Example 2 of the present application;
[0032] Figure 7 Charge-discharge curve of button cell prepared by the sodium supplement additive of Comparative Example 4 in Test Example 2 of the present application;
[0033] Figure 8 Charge-discharge curve of button cell prepared by the sodium supplement additive of Comparative Example 5 in Test Example 2 of the present application;
[0034] Figure 9 Charge-discharge curve of button cell prepared by the sodium supplement additive of Comparative Example 6 in Test Example 2 of the present application;
[0035] Figure 10 Charge-discharge curve of button cell prepared by the sodium supplement additive of Comparative Example 7 in Test Example 2 of the present application. DETAILED DESCRIPTION
[0036] The present application will be further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present application and implement it. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. It should be understood that the specific embodiments are only used to explain the present application, but the embodiments are not limiting to the present application.
[0037] In the present application, unless otherwise specified, the technical and scientific terms used in the present application have the same meanings as those commonly understood by the person skilled in the art to which the present application belongs.
[0038] In the present application, unless otherwise specified, the term "and / or" used in the present application includes any and all combinations of one or more related listed items.
[0039] In the present application, unless otherwise specified, the experimental methods used in the present application are conventional methods, and the materials, reagents, etc. used, if not specifically stated, can be obtained from commercial channels.
[0040] In the present application, unless otherwise specified, the potassium dihydrogen phosphate solution used in the present application is prepared by dissolving potassium dihydrogen phosphate in water, stirring uniformly, and obtaining a potassium dihydrogen phosphate solution with a concentration of 136 g / L.
[0041] In the present application, unless otherwise specified, the preparation of the sodium nickel manganese oxide positive electrode material used in the present application includes the following steps: weighing 36.1 g of sodium carbonate, 62.5 g of nickel manganese hydroxide (mass ratio 3:7), 12.0 g of titanium dioxide, and 6.1 g of magnesium oxide, adding about 100 g of polyurethane balls, using a ball mill at 250 rpm for 4 h to obtain a mixed powder, placing the mixed powder in a muffle furnace for calcination at 900℃ for 10 h with a heating rate of 2℃ / min, and using compressed air at a flow rate of 150 mL / min to obtain a sodium nickel manganese oxide positive electrode material Na 0.67 (Ni 0.33 Mn 0.67 ) 0.7 Ti 0.15 Mg 0.15 O2.
[0042] Example 1
[0043] The sodium supplement additive and the preparation method thereof of the present embodiment specifically include the following steps:
[0044] S1, according to the mass ratio of 1:0.02, sodium citrate and carbon nanotubes are dissolved in ethanol (the mass ratio of material and ethanol is 3:1), and the ball mill is mixed at a speed of 300 r / min for 3 h; then in a tube furnace, first heat at a rate of 2℃ / min to 30℃ and keep for 1 h, let nitrogen fill the tube furnace, then heat at a rate of 2℃ / min to 160℃, and keep for 4 h, then naturally cool to room temperature, to obtain sodium citrate loaded carbon nanotubes C6H5Na3O7-CNTs;
[0045] S2, the sodium citrate loaded carbon nanotubes C6H5Na3O7-CNTs were dissolved in ethanol (mass ratio of material and ethanol was 3:1), under the protection of nitrogen, potassium dihydrogen phosphate solution was added (mass ratio of sodium citrate loaded carbon nanotubes and potassium dihydrogen phosphate was 95:5), stirring reaction for 2h, baking in vacuum drying oven 120℃ for 6h, taking out and grinding, to obtain sodium supplement additive C6H5Na3O7-CNTs@KH2PO4.
[0046] Example 2
[0047] The same as example 1, except that the potassium dihydrogen phosphate was replaced by sodium dihydrogen phosphate.
[0048] Example 3
[0049] The same as example 1, except that the potassium dihydrogen phosphate was replaced by calcium dihydrogen phosphate.
[0050] Comparative example 1
[0051] The same as example 1, except that the potassium dihydrogen phosphate coating was not carried out.
[0052] Comparative example 2
[0053] The same as example 1, except that the potassium dihydrogen phosphate was replaced by aluminum dihydrogen phosphate.
[0054] Comparative example 3
[0055] The same as example 1, except that the potassium dihydrogen phosphate was replaced by dipotassium hydrogen phosphate.
[0056] Comparative example 4
[0057] The same as example 1, except that the carbon nanotube carrier was not used.
[0058] Comparative example 5
[0059] The same as example 1, except that the carbon nanotubes were replaced by activated carbon.
[0060] Comparative example 6
[0061] The same as example 1, except that the sodium citrate was replaced by sodium oxalate.
[0062] Comparative example 7
[0063] The same as example 1, except that the protection of nitrogen in S2 was replaced by air.
[0064] Test example 1
[0065] The pH meter (Lei magnet PHS-25) was calibrated with three solvents, namely potassium biphthalate (pH 4.00), mixed phosphate (pH 6.86), and sodium tetraborate (pH 9.18). After the solvents were prepared, the pH was adjusted to the standard pH of the solvent. Then, 5 g of the positive electrode material (4.5 g of sodium nickel-manganese acid positive electrode material, and 0.5 g of sodium supplement additive of examples 1-3 and comparative examples 1-7) was mixed with 45 g of deionized water, and then the mixture was stirred in a magnetic stirrer. The pH of the mixture was tested by the pH meter, and the results are shown in Table 1.
[0066] Table 1
[0067] Test Sample pH Example 1 11.95 Example 2 11.82 Example 3 11.34 Comparative Example 1 12.38 Comparative Example 2 11.11 Comparative Example 3 12.41 Comparative Example 4 12.02 Comparative Example 5 12.05 Comparative Example 6 10.98 Comparative Example 7 12.19
[0068] As can be seen from Table 1, the sodium supplement additive of the examples can reduce the residual alkali value of the positive electrode material. The sodium citrate in the sodium supplement additive is slightly alkaline, which can slightly raise the pH of the system. However, the potassium dihydrogen phosphate in the same component is weakly acidic, which can neutralize the alkali immediately in the slurry stage, thereby reducing the residual alkali value of the positive electrode material as a whole. Maintaining the sodium ion battery positive electrode material in a neutral environment is to avoid the phase change, corrosion or interface deterioration caused by non-neutral conditions: the metal dissolution of the high-voltage positive electrode is intensified in acidic conditions, and the surface functional groups of hard carbon are damaged in alkaline conditions; the SEI film is highly sensitive to the pH of the electrolyte, and the film is too thick or loose in an excessively acidic environment, increasing the interface impedance, and the film is unstable and induces sodium dendrites in an excessively alkaline environment; the electrolyte is easily decomposed in an extreme pH, and the NaPF6 / carbonate system releases HF and other corrosive byproducts to corrode the electrode; at the same time, the adhesives such as PVDF are degraded and fall off in strong alkali, leading to electrode pulverization, increased internal resistance and decayed rate performance, so the neutral environment is a necessary condition for considering the electrode structure, interface stability and electrolyte integrity.
[0069] As can be seen from the comparison of comparative example 1 and example 1, the residual alkali value of the sodium supplement additive without coating potassium dihydrogen phosphate increases.
[0070] As can be seen from the comparison of comparative example 2 and example 1, when the potassium dihydrogen phosphate is replaced by aluminum dihydrogen phosphate, the pH value of the sample decreases more obviously than that of the conventional sample, because aluminum dihydrogen phosphate has strong acidity.
[0071] As can be seen from the comparison of comparative example 3 and example 1, when the potassium dihydrogen phosphate is replaced by dipotassium hydrogen phosphate, the pH of the sample increases compared with that of the conventional sample, because the pH value of dipotassium hydrogen phosphate is between 8.5 and 9.5, which belongs to alkaline material, so the material as a whole presents alkaline.
[0072] As can be seen from the comparison of comparative example 4 and example 1, when the carbon nanotube carrier is not used, the pH value of the sample has no great difference compared with that of the sample of example 1.
[0073] Comparing Example 1 and Comparative Example 5, it can be seen that when the carbon nanotubes are replaced by activated carbon, the pH value of the sample is not significantly different from that of Example 1.
[0074] Comparing Example 1 and Comparative Example 6, it can be seen that when sodium citrate is replaced by sodium oxalate, the pH value of the sample is significantly lower than that of Example 1, because the pH value of sodium oxalate is about 1.3-2.06, which has strong acidity.
[0075] Comparing Example 1 and Comparative Example 7, it can be seen that when the nitrogen protection process is replaced by air, the pH value of the sample is slightly higher than that of Example 1.
[0076] Test Example 2
[0077] The sodium supplement additives prepared in Examples 1-3 and Comparative Examples 1-7 are made into button cells, wherein the weight ratio of the positive electrode components is sodium nickel manganese oxide positive electrode material:sodium supplement additive:conductive agent(acetylene black):binder(PVDF)=85:5:5:5; and the negative electrode uses sodium sheet. The first circle charge specific capacity and charge-discharge curve of the button cell are tested: the battery is charged at 0.2C constant current to 4.25V in a 25°C constant temperature box, then charged at 4.25V constant voltage until the current is less than 0.02C, and then discharged at 0.2C constant current until the voltage drops to 2.0V. The second circle is charged at 0.5C constant current to 4.25V in a 25°C constant temperature box, then charged at 4.25V constant voltage until the current is less than 0.02C, and then discharged at 0.5C constant current until the voltage drops to 2.0V. The third circle is charged at 1.0C constant current to 4.25V in a 25°C constant temperature box, then charged at 4.25V constant voltage until the current is less than 0.02C, and then discharged at 1.0C constant current until the voltage drops to 2.0V.
[0078] The relevant performances finally measured are shown in Table 2 and Figures 1-10
[0079] Table 2
[0080] Test Sample Initial charge specific capacity (mAh / g) Example 1 120.70 Example 2 119.30 Example 3 119.29 Comparative Example 1 115.75 Comparative Example 2 114.69 Comparative Example 3 113.82 Comparative Example 4 114.33 Comparative Example 5 110.01 Comparative Example 6 103.42 Comparative Example 7 107.85
[0081] From Table 2 and Figures 1-10 It can be seen that the button cells prepared by the sodium supplement agents of the examples have excellent first circle charge specific capacity and charge-discharge performance. This is because the sodium citrate molecule contains 3 sodium ions, and the sodium mass fraction is as high as about 19.5%, which can effectively supplement the sodium loss during the battery cycle and improve the initial capacity. During the electrode preparation(such as slurry coating) or the first charging of the battery, sodium citrate can be decomposed by heating or electrochemically, releasing sodium ions and generating carbonaceous residues(such as amorphous carbon), which enhances the conductivity of the electrode.
[0082] Comparative Example 1-3 can be seen: the performance data of the button cell of Example 1 is slightly better than sodium dihydrogen phosphate and calcium dihydrogen phosphate. This is because the ionic radius of potassium ion, sodium ion, calcium ion is 1.38, 1.02, 1.00, and potassium dihydrogen phosphate promotes the migration of sodium ions by expanding the material layer spacing or forming a more open crystal structure. Among them, sodium dihydrogen phosphate slightly inhibits the migration of sodium ions due to the same ion effect, sodium ions compete with sodium ions in the electrolyte, and calcium dihydrogen phosphate slightly hinders the transmission of sodium ions due to the strong electrostatic effect of divalent calcium ions.
[0083] Comparative Example 1 and Comparative Example 1 can be seen that when potassium dihydrogen phosphate is not coated, the overall material is slightly alkaline, and the electrical performance decreases obviously. This is because the alkalinity will accelerate the decomposition of the electrolyte, corrode the electrode surface, and form an unstable SEI film. Under alkaline conditions, sodium citrate undergoes hydrolysis or oxidation, especially at high pressure, resulting in degradation of organic components, decreased sodium supplement capacity, and oxidation of CNTs in alkaline environment, which can destroy the conductive network and increase the internal resistance.
[0084] Comparative Example 1 and Comparative Example 2 can be seen that when potassium dihydrogen phosphate is replaced by aluminum dihydrogen phosphate, the overall pH value of the material is low due to the strong acidity of aluminum dihydrogen phosphate. Strong acidity can cause sodium citrate to decompose excessively (such as carboxyl removal), destroy the material structure or corrode the CNTs surface. In addition, the high charge density of trivalent aluminum ions can be adsorbed on the surface of CNTs, repelling sodium ions and causing the interface ion conductivity to decrease.
[0085] Comparative Example 1 and Comparative Example 3 can be seen that when potassium dihydrogen phosphate is replaced by potassium hydrogen phosphate, the overall material is slightly alkaline, and the electrical performance decreases obviously. This is because the pH value of potassium hydrogen phosphate in aqueous solution at room temperature is about 8.5-9.5, which is also slightly alkaline.
[0086] Comparative Example 1 and Comparative Example 4 can be seen that when carbon nanotubes are not used as carriers, the electrical performance decreases obviously. This is because the carboxyl and hydroxyl groups on the surface of CNTs act as Na + adsorption sites to reduce the diffusion energy barrier, and the nanometer pores and lumen form a rapid channel to inhibit high-rate polarization; the high aspect ratio and interwoven network structure of CNTs provide a continuous electronic path for insulating sodium citrate and reduce the electrode resistance; at the same time, the hydrophobicity and chemical inertness of CNTs can inhibit the decomposition of the electrolyte and promote the formation of a thin and stable SEI film.
[0087] Comparative Example 1 and Comparative Example 5 can be seen that when carbon nanotubes are replaced by activated carbon, the electrical performance further decreases. This is because activated carbon is a porous amorphous carbon with poor electrical conductivity, and the particles rely on point contact, resulting in a tortuous electronic transmission path and an increase in the overall internal resistance of the electrode. This can cause insufficient electronic contact of sodium citrate and a decrease in utilization. In addition, activated carbon has a high specific surface area (500m 2 / g-3000m 2 / g), which will result in poor electrolyte wettability and some pores cannot be effectively utilized. In this case, the initial capacity may be similar to that of carbon nanotube materials, but the capacity decay is faster at high rates.
[0088] As can be seen from the comparison between Comparative Example 1 and Comparative Example 6, when sodium citrate is replaced by sodium oxalate, the electrical performance is still poor. This is because although sodium oxalate provides two Na + ions per molecule, oxalate is easy to oxidize and decompose, and when it decomposes, all Na + ions will be released at once, causing a sudden increase in local Na + ion concentration, which is easy to induce uneven deposition and side reactions; the oxidation and decomposition of oxalate requires a higher voltage (>4.5V), and in practical applications, the early oxidation of the electrolyte leads to insufficient utilization of sodium; sodium oxalate has strong reducing properties, which will cause the electrolyte to be reduced and generate a thick and uneven SEI film.
[0089] As can be seen from the comparison between Comparative Example 1 and Comparative Example 7, when nitrogen protection is replaced by air protection during the preparation of the material, the electrical performance is poor. This is because O2 will oxidize CNTs to generate CO2 / CO, resulting in the destruction of the structure of CNTs and the loss of electrical conductivity; if the temperature control is not proper, CNTs will be completely ablated, leaving only inorganic residues (such as sodium carbonate or metal oxides). In addition, sodium citrate will gradually decompose when heated in air, and the final product is sodium carbonate and a small amount of carbon residue, losing the organic active ingredient.
[0090] Obviously, the above examples are only examples for the purpose of clarity and do not limit the embodiments. For those skilled in the art, other different forms of changes or variations can be made on the basis of the above description. Here, it is not necessary and impossible to exhaust all embodiments. The obvious changes or variations derived therefrom are still within the protection scope of the present application.
Claims
1. A sodium replenishing additive characterized in that, The sodium supplement additive comprises a substrate and a coating layer coated on the surface of the substrate; the substrate comprises carbon nanotubes and sodium citrate loaded on the carbon nanotubes; and the coating layer is a dihydrogen phosphate; The mass ratio of the substrate to the coating layer is (90-99):(10-1); The mass ratio of the carbon nanotubes to the sodium citrate is (0.01-0.05):
1.
2. The sodium supplement of claim 1, wherein, The dihydrogen phosphate is selected from one or more of sodium dihydrogen phosphate, potassium dihydrogen phosphate and calcium dihydrogen phosphate.
3. The method for producing a sodium supplement according to claim 1 or 2, characterized by, The method comprises the following steps: S1. Ball-milling carbon nanotubes and sodium citrate in ethanol to obtain sodium citrate-loaded carbon nanotubes through heat treatment; S2. Dissolving the sodium citrate-loaded carbon nanotubes in S1 in ethanol, adding a dihydrogen phosphate under a protective atmosphere to react, and drying to obtain the sodium supplement additive.
4. The method of claim 3, wherein the sodium supplement is prepared by, In S1, the rotation speed of the ball-milling is 200 r / min-400 r / min, and the time is 2 h-4 h.
5. The method of claim 3, wherein the sodium supplement is prepared by the steps of: In S1, the heat treatment is first raising the temperature to 30-40℃ at a rate of 1℃ / min-2℃ / min and maintaining for 55 min-65 min, and then raising the temperature to 155℃-165℃ at a rate of 1℃ / min-2℃ / min and maintaining for 3 h-6 h under a protective atmosphere.
6. The method of claim 3, wherein the sodium supplement is prepared by the steps of: In S2, the reaction time is 1 h-4 h.
7. The method of claim 3, wherein the sodium supplement is prepared by the steps of: In S2, the drying temperature is 115℃-125℃, and the time is 4 h-8 h.
8. A sodium-ion battery cathode, characterized in that, The sodium supplement additive of claim 1 or 2, sodium ion battery positive electrode material 70-85 parts, conductive agent 1-10 parts and binder 1-10 parts by mass.
9. The sodium-ion battery cathode of claim 8, wherein, The sodium ion battery positive electrode material is selected from one or more of sodium nickel manganese acid, sodium nickel iron manganese acid, iron sulfate, sodium vanadium phosphate, copper iron manganese acid sodium and sodium iron pyrophosphate; the conductive agent is one or more of carbon nanotubes, acetylene black, conductive carbon black, conductive graphite, carbon fiber and graphene; and the binder is one or more of polyolefin, fluorine-containing resin, polypropylene resin and rubber.
10. A sodium-ion battery, characterized in that, The sodium ion battery positive electrode of claim 8 or 9.
Citation Information
Patent Citations
Preparation method and application of carbon-coated sodium vanadyl phosphate
CN112978702A
Composite lithium / sodium supplementing agent as well as preparation method and application thereof
CN117878451A
Composite sodium supplementing agent, sodium ion battery positive plate and preparation method of sodium ion battery positive plate
CN119627100A
Double-layer coated composite sodium supplementing agent for sodium ion battery as well as preparation method and application of double-layer coated composite sodium supplementing agent
CN120015836A
Composite lithium-supplementing material and preparation method therefor, positive electrode sheet, battery and electric device
WO2025091926A1